Electromagnetic Field Scattering of a High Speed Moving Source and Its Application - Sahrani, Shafrida; Isa, Nor Shafrillah; Anak Hong Ping, Kismet; Akata, Tatsuya; Kuroda, Michiko (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
This paper presents the electromagnetic (EM) field scattering of a high speed moving source and a moving target by using Finite-Difference Time-Domain (FDTD) with Overset Grid Generation (OGG) method. The analysis is conducted for 750MHz band at the street intersection with OpenMP parallel processing technique. The performance of this proposed method is verified with theoretical results. The simulation results have shown comparatively good agreement in moving and stationary case. The proposed simulation study is of great importance to ground transportation in Intelligent Transportation System (ITS) applications.